New modified tanh-function method for nonlinear evolution equations - Wafaa M. Taha; Abbas H. Kadhim; Raad A. Hameed; M. S. M. Noorani (Tikrit Journal of Pure Science)
The aim of this paper is to calculate the Traveling waves solutions by using a new technique which is called modified tanh-function method, which are successfully performed  to get analytical solutions for  Korteweg-deVries (KdV)–Burgers’ equation and (2+1)-dimensional Calogero–Bogoyavlenskii–Schiff (CBS) equation. As a result, when the equation parameters are taken as special values, some new solitary wave solution are obtained. Moreover we find in this work that the modified tanh-function method give some new results which are easier and faster to compute by the help of a symbolic computation system. The results obtained were compared with standard  tanh-function method.